2016
DOI: 10.21649/akemu.v22i3.1405
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy in Hyperbilirubinemic Neonates; Does it Affect Platelet Count?

Abstract: <p><strong>Objective:</strong><strong>  </strong>To determine the effect of phototherapy on platelet count in neonates having unconjugated hyperbilirubinemia.</p><p><strong>Patients and Methods:</strong><strong>  </strong>This cross sectional study was conducted in the Neonatology unit of a Hospital, Faisalabad during a period of nine months i.e., January to September 2015. All the neonates having unconjugated hyperbilirubinemia and requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
2
7
0
2
Order By: Relevance
“…This finding is in contrast to present and previous studies. [2][3][4][5]8,10 They further reported that the most significant decline in platelet counts was in 24 hours PT duration compared to the 48 hours this finding is strongly supportive to the present study as it has noted similar observations. Pishva et al 14 reported very high incidence of 49.5% of thrombocytopenia of total 101 neonates after PT.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This finding is in contrast to present and previous studies. [2][3][4][5]8,10 They further reported that the most significant decline in platelet counts was in 24 hours PT duration compared to the 48 hours this finding is strongly supportive to the present study as it has noted similar observations. Pishva et al 14 reported very high incidence of 49.5% of thrombocytopenia of total 101 neonates after PT.…”
Section: Resultssupporting
confidence: 88%
“…This is in accordance to the previous studies. [2][3][4][5]8,10 Venaktamurthy et al 10 reported similar observations of platelet counts. They reported a decline in platelet counts in total study population after PT, but the difference was non-significant except in low birth babies.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Também foi decaindo o número de recém-nascidos que não apresentavam nenhum grau de trombocitopenia, por volta de 50%, atingindo cerca de 33% dos pacientes. É importante salientar que nenhum recémnascido apresentou sintomas da baixa contagem de plaquetas (Sajid, et al;. Esses estudos também reforçam a ideia de que a fototerapia influencia no sistema imunológico do recém-nascido (Zarkesh, et.…”
Section: Resultsunclassified